The Post-Colonial Phenomenon in Central and Eastern European Film Production – the Special Case of Hungarian Filmmakers in Romania - Anna Kós (Symbolon)
In the last decade the phenomenon of post-colonialism, transnationalism and trans-culturalism in film production have become increasingly prominent areas of research; this is a logical consequence of globalization in general, amplified at the same time by the spread of co-production budgets increasingly common in arts that require a large financial outlay involving several countries. In my study I focus on the productions of Hungarian filmmakers in Transylvania: directors here have never been the favorites of film financing bodies (from the Soviet Union at the beginning, from the EU countries later, respectively from Romania or Hungary in general), needing the support of several countries in order to make a demanding and professional film. I am trying to find out whether the cultural characteristics of the entities participating in the funding, such as states, regions, communities, appear in the productions made in this way and if so, in what form.